Pendampingan Bagi Orang Tua mengenai Pola Asuh positif dalam Membentuk Karakter Anak di Desa Banjarejo Kota Madiun - Silvia Yula Wardani; Rischa Pramudia Trisnani (Jurnal SOLMA, 2023)
Character is a description of a child's behavior that can be judged from the norms that apply in society. Characters that must be formed from an early age include mutual respect, obedience, courtesy and courtesy and democracy. Efforts made to form good character in children require parenting. Positive parenting is important for parents as an effort to shape children's character, make children more communicative and support children's development to the fullest. This encourages the community service team to provide knowledge related to positive parenting to shape the character of children in Banjarejo Village, Madiun City. In community service activities, we partnered with Banjarejo Village, Madiun City, with 35 parents accompanying participants who joined the Toddler Posyandu activities. The servant provides material related to good character in children and how to form good character in children through positive parenting. The evaluation results show that after mentoring, parents gain new knowledge about character and positive parenting. This activity helps parents by providing knowledge in carrying out positive parenting for children so that children have good character. It is hoped that this new knowledge can be applied by parents in raising children so that children have good character.